Avaliação do sombreamento e da iluminação natural em apartamentos de edifícios residenciais verticais multifamiliares de Maceió-AL: o uso de varandas. - Carvalho, Camila Antunes de (2010)
In regions with hot and humid tropical climate, as Maceió-AL, the use of daylight, natural ventilation and shading should be thought from the initial stages of the project. To enhance shading, architectural elements as brises-soleil, perforated blocks and balconies are essential to buildings. In the case of balconies, today we see the use of random on environmental issues. As a consequence, and solution for the discomfort caused by the absence of appropriate elements of weather, the use of artificial means to ensure the thermal and visual comfort is intensified contributing to wasted energy. Given this context, this study aims evaluat the use of balconies in vertical multifamily residential apartments buildings located in Ponta Verde, Maceió-AL, as shading and daylighting. To achieve this, the methodology was a comparative analysis of recurring types of balconies on the shading and daylight devices, through the techniques of data collection, generation of shadow masks and simulations in the program Sketchup and Tropilux. The analysis of results provided an understanding of the behavior of shading and daylighting in the typologies examined and also the comparison between the simulation results of heatstroke and the results of simulation of daylighting. Since opting for a better strategy of shading, using the balconies, it is not always achieved a good result in the performance of daylight indoors. Finally, the use of balconies in residential buildings of Maceió, that can be worked to achieve better results in environmental comfort and to enrich the formal aspect of the buildings, should be considered at an early stage of the architectural design